1990
DOI: 10.1126/science.2237407
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Mice Against the Lyme Disease Agent by Immunizing with Recombinant OspA

Abstract: Lyme borreliosis is a tick-borne illness caused by Borrelia burgdorferi. The gene for outer surface protein A (OspA) from B. burgdorferi strain N40 was cloned into an expression vector and expressed in Escherichia coli. C3H/HeJ mice actively immunized with live transformed E. coli or purified recombinant OspA protein produced antibodies to OspA and were protected from challenge with several strains of B. burgdorferi. Recombinant OspA is a candidate for a vaccine for Lyme borreliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
372
3
4

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 466 publications
(386 citation statements)
references
References 18 publications
7
372
3
4
Order By: Relevance
“…The finding that the transmission of B. burgdorferi organisms to ticks correlated inversely with the presence of antibodies to OspA and OspB in mice therefore suggests that these antibodies are responsible for the elimination of spirochetes and consequently for the reduction in the rate of transmission. This assumption is also supported by previous studies showing that OspA-and OspB-specific antibodies protect SCID [4,5] and C3H/HeJ mice [6,7] against infection and development of arthritis after experimental and tick-mediated infection with B. burgdorferi, when these antibodies are present at the time of inoculation [13,14].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The finding that the transmission of B. burgdorferi organisms to ticks correlated inversely with the presence of antibodies to OspA and OspB in mice therefore suggests that these antibodies are responsible for the elimination of spirochetes and consequently for the reduction in the rate of transmission. This assumption is also supported by previous studies showing that OspA-and OspB-specific antibodies protect SCID [4,5] and C3H/HeJ mice [6,7] against infection and development of arthritis after experimental and tick-mediated infection with B. burgdorferi, when these antibodies are present at the time of inoculation [13,14].…”
Section: Discussionsupporting
confidence: 72%
“…In mice, hamsters, and white-footed mice (Perornyscus leucopus), the first antibodies detected were those to the outer surface proteins (Osp) A and B, to a 39-kDa protein, and to the 41-kDa flagellin (fla) [1][2][3]. It was subsequently shown that antibodies specific for OspA and OspB are protective and able to prevent B. burgdorferi-induced disease in immunodeficient SCID [4,5] and immunocompetent C3H/HeJ mice [6,7].…”
Section: Mode Of Inoculation Of the Lyme Disease Agent Borrelia Burgdmentioning
confidence: 99%
“…burgdorferi N40 OspA mAb C3.78, which can protect mice from spirochete infection, was purified from a C3.78-producing hybridoma culture supernatant (16). Supernatant (40 ml) was passed over a 0.5-ml protein A column (Bio-Rad Laboratories, Hercules, CA) that then was washed twice with 20 ml of PBS, pH 7.4.…”
Section: Antisera and Mabmentioning
confidence: 99%
“…22). Rabbit antisera against recombinant OspA-, OspF-, and OspE-related protein (Erp) T from B. burgdorferi N40 have been described previously by our group (16,28,29). OspF is encoded by a member of a multigene family (erps) that are differentially expressed throughout the B. burgdorferi life cycle (30).…”
Section: Antisera and Mabmentioning
confidence: 99%
See 1 more Smart Citation